O desempenho institucional do Executivo no Legislativo entre 2002 e 2006 - Santos, Rodrigo dos (2007)
This master thesis analyses the interplay of political powers in Brazilian Legislative chambers, during Lula s government. It considers the point of view of the parties and the interests present on budget and fiscal disputes between Federal Executive power and State Executive powers. It is considered that, as a representative and supervisory institute, the Legislative chambers offer the possibility of politic interactions between Executive power, governors and parties. The analysis follows eight budget initiatives, being four of Crédito Extraordinário (Extraordinary Credit) and four of Auxílio Financeiro (Financial Aid), made through Medidas Provisórias (Provisory Measures) by the Executive power in benefit of States, towns and cities, after some partial constitutional modifications, known as the Amendment n° 32, were implemented. After the identification of the gaps existing both in studies that stress the centralization of legislative works and studies that emphasize the individual and regional members of parliament s behavior, this study stresses the need for initiatives of the Executive power that consider the tributary increase of other government instances. It is argued that the Executive can, strategically, co-ordinate his initiatives with the other government instances in an interactive way, to strengthen the Federal Government and to promote modifications in the current model of fiscal exaction. The analysis of the data shows that the Executive power, in spite of assuming the need for a reformulation of the fiscal model, avoids the influence of the Legislative power, particularly that of the Senate, driving bigger resources for Crédito Extraordinário, in detriment of Auxílio Financeiro. It concludes that the difficulties found by the Executive power to approve a new model of fiscal exaction in the Legislative chambers can be associated with little influence of the government party (PT) on state governments.